Residents’ perception of the benefits of cultural tourism: the case of Guimarães - Vareiro, Laurentina (2013)
In many cities throughout Europe and the rest of the world, cultural tourism plays a major role in local economic development. Tourism also acts to preserve cultural heritage, as it provides a way to acquire the revenue needed to restore and preserve historical buildings, and encourages local people to value their traditions and festivals. However, tourism success can be a double-edged sword with tourist flows having a strong impact on the quality of life of residents when certain tourist thresholds are surpassed. This paper aims to address local residents’ perception of the benefits of cultural tourism. To capture their perception, a survey was implemented, addressed to both the city centre inhabitants and the non-urban residents of the Guimarães municipality.